Implementasi Pembelajaran Berdiferensiasi dalam Mengembangkan Karakter Siswa Sekolah Dasar: Kajian Literatur Sistematis - Vini Anandita Adha; Fathia Az-Zahra Nazfa; Feby Natasya; Azzahra Julaika; Yuricha Nadwa At-Tazkia Rambe; Asna Istikmalatul Muktamaroh (Jurnal Keluarga Sehat Sejahtera, 2026)
Differentiated curriculum is an instructional approach that adapts the learning process based on students’ needs, readiness, interests, and learning profiles. In diverse elementary school learning environments, the implementation of a differentiated curriculum becomes an important strategy to accommodate students’ varying characteristics. In addition to improving academic learning outcomes, this approach also plays a role in developing students’ character values such as discipline, responsibility, cooperation, tolerance, self-confidence, and empathy. This study aims to examine the implementation of a differentiated curriculum in developing character values of elementary school students in diverse learning environments. The research method used is library research, by analyzing various sources such as books, scientific journals, and educational policy documents. The findings indicate that differentiated learning is able to create an inclusive, active, and enjoyable learning environment, and is effective in instilling character values through collaborative activities, the provision of task choices, project-based learning, and self-reflection. Therefore, the implementation of a differentiated curriculum can serve as a relevant learning solution in shaping the character of elementary school students amidst diverse learning environments.